3f-4-5f=f+4+5

Simple and best practice solution for 3f-4-5f=f+4+5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3f-4-5f=f+4+5 equation:


Simplifying
3f + -4 + -5f = f + 4 + 5

Reorder the terms:
-4 + 3f + -5f = f + 4 + 5

Combine like terms: 3f + -5f = -2f
-4 + -2f = f + 4 + 5

Reorder the terms:
-4 + -2f = 4 + 5 + f

Combine like terms: 4 + 5 = 9
-4 + -2f = 9 + f

Solving
-4 + -2f = 9 + f

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Add '-1f' to each side of the equation.
-4 + -2f + -1f = 9 + f + -1f

Combine like terms: -2f + -1f = -3f
-4 + -3f = 9 + f + -1f

Combine like terms: f + -1f = 0
-4 + -3f = 9 + 0
-4 + -3f = 9

Add '4' to each side of the equation.
-4 + 4 + -3f = 9 + 4

Combine like terms: -4 + 4 = 0
0 + -3f = 9 + 4
-3f = 9 + 4

Combine like terms: 9 + 4 = 13
-3f = 13

Divide each side by '-3'.
f = -4.333333333

Simplifying
f = -4.333333333

See similar equations:

| 15x^2=100 | | -20n+6(16+16n)=-12(n-8) | | 3y^2=-7-4 | | -21y=-765 | | 3n+18=-24 | | 2x^7/2x^3/13 | | 1/3(9x+5)=5(x-1)-6 | | 4b^2+(-7)b=0 | | 2a+6=a-8 | | f(x)=2x^2-5x-3 | | -3h+4.2=55-11h | | 6+(3x-3)=2 | | 3x+5-3x=4x-2 | | 3x+5-3x=4x-2 | | -10+p/9=-11 | | -9(x+6)=-54 | | 1/5s=2 | | 8x^2-22x-90=0 | | 7mx^2+2nx^2-7my^2-2ny^2=0 | | 7/5-3/8(136/15)=-2 | | 25+4(-4x+5)= | | 14z=0 | | 8/3x^2-5/4x | | 1/2x=11/14+4/7 | | 7/5-3/8(136/15) | | 17-(6x+3)-2x+4= | | ((3(x-4)/4)/4)=4x-4 | | 6a^2+27a-15=0 | | 7x+2y=26 | | 75/3*25= | | 10w-14wv-15w+21v=0 | | 3(x-8)=4(x+2) |

Equations solver categories